P133 Adrenal insufficiency in severe asthma: an emerging problem in the era of biologic therapies. (December 2018) - Raheem, A; Green, L; Fernandes, M; Roxas, C; d'Ancona, G; Kavanagh, J; Kent, BD; Jackson, DJ
Abstract : Background: The association between chronic oral corticosteroid (OCS) treatment in asthma and adrenal insufficiency (AI) is well described. With the recent introduction of anti-IL-5 therapies many patients are for the first time able to significantly reduce or eliminate the need for continuous OCS. A predictable but under-appreciated consequence of this has been the challenge of AI. To date, an analysis of the size and prevalence of this clinical problem has not been carried out. Method: A retrospective review of OCS-dependent asthmatics treated with mepolizumab at Guy's Severe Asthma Centre was performed with the aim of quantifying the prevalence of AI in patients able to reduce their OCS dose to <5 mg/day of prednisolone. Adrenal function was assessed by morning blood cortisol levels which were repeated at 4-weekly intervals if the initial measurement was below the normal range. Patient reported symptoms compatible with AI were recorded along with baseline clinical characteristics including duration and dose of OCS treatment. Results: Eighty-two patients with severe OCS-dependent eosinophilic asthma treated with mepolizumab were identified. Of these, 37 were able to reduce their maintenance OCS dose <5 mg/day and were assessed for evidence of AI. 23/37 (62.1%) had evidence of AI based on suppressed morning cortisol levels. By 16 weeks, 10/23 (43.5%) had normalised their cortisol levels and were asymptomatic. 13/23 (56.5%) demonstrated ongoing evidence of AI beyond 16 weeks. Interestingly neither the initial dose of OCS nor duration of OCS use predicted the likelihood of AI. Conclusion: Evidence of adrenal insufficiency is apparent in over 60% of patients on biologic treatments able to successfully wean their prednisolone to <5 mg/day. Over half of these patients remain insufficient at 16 weeks highlighting a common and largely unreported problem. Appropriate guidelines need to be produced to inform clinicians managing AI in severe asthma.